Pengembangan Aplikasi Buku Tamu Berbasis Web di BPTIK DIKBUD Jawa Tengah - Dzalparo, Ajis; Prihati, Yani; Yusup, Yusup (STMIK Banjarbaru, 2024)
The Center for the Development of Information and Communication Technology in Education and Culture (BPTIK DIKBUD) of Central Java supports the Department of Education and Culture of Central Java Province in information technology. The visitor data recording system previously faced security issues. This research develops a web-based guestbook system to enhance security, redesign the interface, and provide accurate and dynamic statistics. The new admin feature allows for full data management, while the dynamic statistics feature collects visit information for evaluation. Development using the waterfall method with HTML, CSS, JavaScript, PHP, and MySQL technology. Testing with black-box testing methods and vulnerability assessments shows that the system is effective in managing data and is secure from vulnerabilities. The new UI/UX design enhances efficiency and user experience. This system is expected to serve as a model for visitor data management and requires ongoing evaluation and development.Keywords: BPTIK DIKBUD Central Java; Guest Book; Waterfall.Â AbstrakBalai Pengembangan Teknologi Informasi dan Komunikasi Pendidikan dan Kebudayaan (BPTIK DIKBUD) Jawa Tengah mendukung Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah dalam teknologi informasi. Sistem pencatatan data pengunjung sebelumnya menghadapi masalah keamanan. Penelitian ini mengembangkan sistem buku tamu berbasis web untuk meningkatkan keamanan, mendesain ulang tampilan, dan menyediakan statistik akurat dan dinamis. Fitur admin baru memungkinkan pengelolaan data penuh, sementara fitur statistik dinamis mengumpulkan informasi kunjungan untuk evaluasi. Pengembangan menggunakan metode waterfall dengan teknologi HTML, CSS, JavaScript, PHP, dan MySQL. Pengujian dengan metode black-box testing dan vulnerability assessment menunjukkan sistem efektif dalam mengelola data dan aman dari celah keamanan. Desain UI/UX yang baru meningkatkan efisiensi dan pengalaman pengguna. Sistem ini diharapkan menjadi model pengelolaan data pengunjung dan memerlukan evaluasi serta pengembangan berkelanjutan.Kata Kunci: BPTIK DIKBUD Jawa Tengah; Buku Tamu; Waterfall.